Gaya Komunikasi Keluarga: Kajian Nasihat Luqman kepada Anaknya dalam al-Qur'an Surah Luqman - Sari, Hijrayanti; Novira, Nuraeni; Hawariah, A (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
The purpose of this study was to answer how Lukman communication patterns to his child. The problem to be deciphered is the interpretation of Lukman's advice to his child. And what communication patterns are used. This research is a library research with a qualitative perspective approach with content analysis techniques. The conclusion obtained is Lukman as a father in the communication process acting as a communicator has credibility with the wisdom given by God. The advice or message used is informative and persuasive. Informative messages are prepared using the deductive order model. His advice to his son conclude that the basis of life about faith, law, morals, destiny and the will of God, and the decree of His hamba, establish prayers, amar ma'ruf nahi munkar, be patient with the misfortune that was revealed to him, be wise and just to fellow human beings , stay away from arrogant nature, interact with humans gently, keep useless talk, and do not speak rudely. While persuasive messages are arranged by emotional appeal.